ANALYSIS OF COMPLIANCE RISK MANAGEMENT THROUGH CUSTOMER DUE DILIGENCE AT BANK SUMUT SYARIAH KCP STABAT - Siti Maysaroh; Sugianto Sugianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study is entitled Analysis of Risk Management through Customer Due Diligence at Bank Sumut Syariah KCP Stabat to answer the formulation of the problem on how to analyze compliance risk management through customer due diligence at Bank Sumut Syariah KCP Stabat. The research method used is qualitative research which produces descriptive data by observing the research object and then analyzing it. The results of this study are that PT Bank Sumut Syariah Stabat Branch Office has policies and procedures regarding the implementation of Customer Due Diligence (CDD) which consist of four procedures, namely identification, verification, monitoring to reporting. PT Bank Sumut Syariah Kcp Stabat has carried out in detail the implementation of Customer Due Diligence(CDD) in accordance with the basic guidelines owned by PT Bank Sumut Syariah Kcp Satabat although the application of these principles sometimes experiences obstacles from various factors. The research method used in this study is a qualitative method that will provide descriptive data by observing the object of research and then analyzing it. Keywords: Customer Due Diligence (CDD) and risk management